Show Me the Value of the Training: Continuing Education for Survival - Ruby Cain (Adult Education Research Conference, 2014)
Each year American Society of Training and Development (ASTD) commissions and publishes a study of training metrics, titled State of the Industry Report. From the 2012 findings, ASTD estimated approximately 164.2 billion was spent on employee training (Miller, 2013). With rapidly changing technology, increasing competition, major shifts in the economy, it is essential that a company maximizes productivity to remain viable. Maximum productivity cannot be achieved without a high performing workforce. Because of the dynamic environment in which companies operate, this requires training and retraining the workforce. Yesterday’s skills can spell the demise of an organization. Training is the answer. And yet, companies are still struggling to maximize productivity. It has been estimated that as much as half of all training expenditures are wasted. What can this be attributed to?